Perspektif Perempuan Dalam Film Mimi Melalui Analisis Wacana Kritis Sara Mills - Dionisius Lesmana; Gabriella Monique Valentina (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2022)
Individual authority can affect the power of other individuals over themselves based on knowledge and experience in society, especially women from marginalized groups in India who are depicted in the Mimi movie which tells the story of a surrogate mother who experiences injustice. The phenomenon against women from marginalized groups is still a long scourge so that an elaboration and understanding of it is needed to solve the occurred problem. The objective of this research is to describe the perspective of women in the Mimi movie through Sara Mills' Critical Discourse Analysis. This research uses a qualitative method through Sara Mills' Critical Discourse Analysis based on the subject, object, and audience’s position. The results of the study show a standpoint that associates the relations of the uppe class society as